Penyuluhan pada Guru Sekolah Dasar tentang Keberadaan Bimbingan dan Konseling - Basuki, Agus; Farozin, Moh; Indriyana Rachmawati (Masyarakat Berdaya dan Inovasi, 2023)
Guidance and counseling in elementary schools is an important foundation for the formation of students' identity towards optimal development. However, currently guidance and counseling is still limited to secondary school level, not yet reaching elementary school. Ideas for guidance and counseling in elementary schools at the cluster level have not been implemented optimally. Therefore, it is necessary to understand the importance of guidance and counseling in elementary schools to understand its existence in helping to overcome students' problems. This service method is carried out synchronously online and offline or face to face. Synchronous online implementation is to identify student problems in elementary schools, while offline or face-to-face implementation consists of providing instructions in the form of materials, modeling and exercises. The results of the service show that class teachers or subject teachers understand the importance of guidance and counseling in elementary schools, shown by an increase in pretest and posttest scores to 92% of teachers understand the need for guidance and counseling in elementary schools.